2016
DOI: 10.2196/humanfactors.4765
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Views on the Perceived Benefits and Drawbacks of Seeking Help for Mental Health Problems on the Internet: A Qualitative Study

Abstract: BackgroundUniversity students experience high levels of mental health problems yet very few seek professional help. Web-based mental health interventions may be useful for the university student population. However, there are few published qualitative studies that have examined the perceived benefits and drawbacks of seeking help for mental health problems on the Internet from the perspective of university students.ObjectiveTo investigate the attitudes of university students on mental health help-seeking on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 19 publications
9
98
2
4
Order By: Relevance
“…In contrast to prior research surrounding the negative impact of using SNSs for information and support [82][83][84][85][86], this study found that people using open Facebook groups felt, on the whole, that the support they received from online peers had a positive impact on feelings of empowerment and hope [76], their perceived social support network [74,75], and feelings of stigmatization were reduced [77]. Based on the observable data from both the UK and the USA, stigma relating to mental illness was shown to be a pervasive factor in people's lives, and both data sets highlighted the following points.…”
Section: Principle Findingscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to prior research surrounding the negative impact of using SNSs for information and support [82][83][84][85][86], this study found that people using open Facebook groups felt, on the whole, that the support they received from online peers had a positive impact on feelings of empowerment and hope [76], their perceived social support network [74,75], and feelings of stigmatization were reduced [77]. Based on the observable data from both the UK and the USA, stigma relating to mental illness was shown to be a pervasive factor in people's lives, and both data sets highlighted the following points.…”
Section: Principle Findingscontrasting
confidence: 99%
“…By sharing personal experiences of their mental illness, Facebook users provided informational and emotional support to other group members that may not be available from the receivers own social network or professionals, in line with previous research [18,19,34]. This form of support may lead to increased feelings of connectedness for the receiver [67,78], and could potentially reduce feelings of social isolation [22][23][24]74], and may offer hope to people using Facebook for their mental illness [76], thus empowering them to seek help or take positive action. From the findings, it was noted that the UK sample tended to show a slightly higher level of self-disclosure.…”
Section: Principle Findingsmentioning
confidence: 66%
See 1 more Smart Citation
“…Some of these findings are broadly similar to previous studies. [18][19] However, the study captured the perceptions of potential clients in India who showed an initial inclination/readiness/felt need to use an internet based self-help program, unlike studies that rely on a general population, most of which have been carried out in other socio cultural contexts. Moreover, the findings also bring to light the fact that individuals who are already in contact with traditional mental health services are also likely to be interested in learning selfhelp methods in order to experience a sense of mastery over challenges related to illness/ engage in actions to prevent future problems and work towards a psychological sense of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…17 Ease of access, privacy and anonymity, flexibility, low effort, convenience and low cost are mentioned as some of the factors that underlie preferences for e-mental health interventions. [18][19] However, deficient e-awareness and ambivalent attitudes have also been reported. 20 Though several structured internet based mental health interventions have been developed and tested for efficacy, the potential public health impact of these programs is unlikely to be realized without wide-scale uptake and optimal rates of completion /adherence.…”
Section: Introductionmentioning
confidence: 99%